Exploring Shah Alam City Council’s commitment towards a low-carbon city / Farah Nadia Azhar, Zarina Mohd Zain and Nor Azira Ayob - Azhar, Farah Nadia; Mohd Zain, Zarina; Ayob, Nor Azira (Universiti Teknologi MARA, Perak, 2025)
Shah Alam, the economic hub of Selangor has undergone rapid urbanization over the years. As a result, it has led to a significant increase in carbon emissions in the city. In response to meeting the global vision for the Sustainable Agenda, Shah Alam City Council (MBSA) has established the Low Carbon City Action Plan which promotes sustainable urban development. This paper explores Shah Alam City Council's commitment through its initiatives and strategies in achieving a low-carbon city. It employs a qualitative analysis through semi-structured interview of MBSA personnel. The result showed that Shah Alam City Council (MBSA) had implemented numerous initiatives through its action plan which is analysed through the urban environment, urban infrastructure, urban transportation, and buildings. However, the lack of financial support and participation by the elderly hinders the full capabilities of a low-carbon city development.